Reflexive processes in the musician performer’s professional activities - Нүсіпжанова, Б. Н. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2015)
The article attempts to identify the gradual development of the category of reflection as one of the driving factors of self-actualization, to reveal meaningful face value and basic directions of its multi-dimensional interpretation. Singer is a profiling nature of reflexive action acts as a basic psychological foundation in professional activities musician, as skilful possession musical material involves search, selection of meanings in finding an appropriate embodiment. Interest in this subject should be considered as an attempt to uncover the deeper nature of reflexive processes actively thinking musician – performer in professional work, to get to his reflexive consciousness in reliance on intelligent mechanisms of the creative nature of the person who devoted himself to art. Appeal to the reflexive process in performing musician as dictated by the need to identify their specificity, understand and grasp the fundamental aspects of the study of properties of reflexive thinking expert in their chosen profession. Key words: reflective processes, a musician – singer, musical – performing activity, music.